The expression of E-selectin and chemokines in the cultured human lymphatic endothelium with lipopolysaccharides - Sawa, Yoshihiko (Blackwell Science Inc, 2008)
This study investigated the expression of selectins and chemokines in cultured human lymphatic endothelial cells stimulated with lipopolysaccharides. In microarray, vascular cell adhesion molecule-1 and intercellular adhesion molecule-1 gene expressions in the lymphatic endothelium with lipopolysaccharides did not change at 0.5 h but increased two- to three-fold at 12 h, whereas E-selectin increased 10-fold at 0.5 h and 68-fold at 12 h compared with untreated cells. The E-selectin mRNA and protein increased in the lymphatic endothelial cells with lipopolysaccharides at more than two-fold levels compared with human umbilical vein endothelial cells. Induction of Cys-Cys chemokine ligand 2, 3, 5, 7, 8 and 20 mRNAs in the lymphatic endothelial cells with lipopolysaccharides was detected in microarray and real-time PCR. The Cys-Cys chemokine ligand 2, 5 and 20 mRNA amounts in cells with high concentration lipopolysaccharides were larger in the lymphatic endothelial cells than in human umbilical vein endothelial cells. The Cys-Cys chemokine ligand 3 and 8 mRNAs were not detected in human umbilical vein endothelial cells. Induction of Cys-X-Cys chemokine ligand 1, 3, 5, 6 and 8 mRNAs was detected in the lymphatic endothelial cells with lipopolysaccharides. The Cys-X-Cys chemokine ligand 3, 5 and 8 mRNA amounts in cells with high concentration lipopolysaccharides were larger in the lymphatic endothelial cells than in human umbilical vein endothelial cells. In conclusion, it was demonstrated that the cultured human lymphatic endothelial cells express E-selectin and phagocyte-attractive chemokine genes.